Sistem Informasi Kependudukan - Ifan Ahmad; Moch Arief Sutisna (Jurnal Sibernetika, 2020)
Developments in the field of information technology, especially website-based information systems, have brought convenience that promises work efficiency both offline and online. Currently, every job in agencies, both government and private, is involved with managing and archiving data. This includes managing population data at the Rukun Warga (RW) and Rukun Tetangga (RT) levels. This study aims to provide solutions through the study of several theories and observations in designing a web-based population information system. The development methodology and application design that the author uses the waterfall method until the testing stage. The programming language used is Sublime Text and the database uses mysql. The research and observations carried out resulted in applications that would facilitate the storage, archiving and searching of population data. The development of this system is very precise, it is proven that it does not take a long time to search for data compared to manual systems. This system still needs a lot of improvement and improvement, therefore constructive input and suggestions are always expected for improvement and development of information systems in the future.